Al-Maraghi's Interpretation and Its Relevance to Contemporary Social Interpretation - Al Masithoh, Silvinatin; Masruhan (International Journal of Islamic Thought and Humanities, 2026)
This study aims to analyze Ahmad Mustafa al-Maraghi's thoughts in his book, Tafsir al-Maraghi, regarding verses on social interaction and assess their relevance to contemporary social issues. The research problem focuses on how al-Maraghi's interpretive methodology explains human interaction and the extent to which this approach is effective in addressing the challenges of a modern pluralistic society. The research method used is library research with a descriptive-analytical approach. Primary data comes directly from the text of Tafsir al-Maraghi, while secondary data is drawn from supporting literature on the adabi ijtima'i interpretation and the sociology of religion. The results show that al-Maraghi's interpretation emphasizes practical values ​​such as religious tolerance, social justice, interfaith cooperation, and ethical communication. Its main characteristics are the use of straightforward language, contextualization of verses with social realities, and an emphasis on morality. Al-Maraghi successfully integrates linguistic and historical analysis with sociological insights, striking a balance between classical tradition and the demands of modernity. In conclusion, Tafsir al-Maraghi is highly relevant as an ethical guide for Muslims seeking to foster harmony and constructive dialogue in a multicultural environment. This model is a prototype for developing contextual Islamic scholarship without abandoning the Koran's basic principles.